ChemInform Abstract: Efficacious N‐Protection of O‐Aryl Sulfamates with 2, 4‐Dimethoxybenzyl Groups. Issue 8 (1st March 2013) - Reuillon, Tristan; Bertoli, Annalisa; Griffin, Roger J.; Miller, Duncan C.; Golding, Bernard T.
Abstract The protection‐deprotection strategy comprises reaction of phenols (I) with sulfonylbis(methylimidazole) (II) to provide aryl imidazole sulfonates (III), which are activated by reaction with trimethyloxonium tetrafluoroborate, before further reaction with the methoxy‐substituted dibenzylamine (IV) or (VII).